VD_FINDINFO HC / 2009 / 313 vom 21. Oktober 2009 - VD Tribunal cantonal (2009)
EXPULSION DE LOCATAIRE, BAIL À LOYER, DEMEURE DU DÉBITEUR, RÉSILIATION IMMÉDIATE, LOYER | 257d CO, 457 al. 1 CPC, 23 LPEBL, 29 LPEBL